Chemopreventive effect of phosphodieasterase-4 inhibition in benzo(a)pyrene-induced murine lung cancer model. (1st December 2014) - Yeo, Chang Dong; Kim, Jin Woo; Ha, Jick Hwan; Kim, Seung Joon; Lee, Sang Haak; Kim, In Kyoung; Kim, Young Kyoon
ABSTRACT Purpose: Cigarette smoking increases chronic airway inflammation, oxidative stress, and epithelial mesenchymal transition (EMT), which may result in chronic obstructive pulmonary disease (COPD) and tumor growth in the lung. Phosphodiesterase 4 (PDE4) inhibitors are known to reduce inflammation, and they have recently been introduced for the treatment of COPD. We assessed the impact of rolipram, a selective PDE4 inhibitor, on chemoprevention in benzo(a)pyrene-induced lung cancer in mice. Materials and Methods: Female A/J mice were given a single dose of benzo(a)pyrene. Intraperitoneal administration of rolipram began 2 weeks post-carcinogen treatment and continued tri-weekly for 28 weeks. Tumor load was determined by averaging the total tumor volume in each group. Results: Benzo(a)pyrene induced an average tumor size of 10.4 ± 1.7 tumors per mouse, with an average tumor load of 25.9 ± 3.8 mm3. Rolipram significantly decreased tumor number, by 45.1%, and tumor load, by 52.9%, compared with the benzo(a)pyrene group. Ki67 staining was reduced in rolipram-treated mice compared with benzo(a)pyrene-treated mice. The increased expression of EMT markers caused by benzo(a)pyrene was inhibited by rolipram. Rolipram significantly attenuated NF-κB and Nrf2 expression in benzo(a)pyrene-induced lung cancer tissues. Conclusions: In vivo experiments in the benzo(a)pyrene-induced model of lung cancer show that PDE4 inhibition significant inhibits lung carcinogenesis. Our results provide evidence that PDE4 inhibitors may be suitable for the prevention of the lung cancer in high-risk groups, for example, heavy smokers and patients with COPD.